The scale of the evidence base on the health effects of conventional yogurt consumption: findings of a scoping review - Glanville, Julie M.; Brown, Sam; Shamir, Raanan; Szajewska, Hania; Eales, Jacqualyn F. (Frontiers in Pharmacology, 2015)
Background: The health effects of conventional yogurt have been investigated for over a century; however, few systematic reviews have been conducted to assess the extent of the health benefits of yogurt. Objective: The aim of this scoping review was to assess the volume of available evidence on the health effects of conventional yogurt. Methods: The review was guided by a protocol agreed a priori and informed by an extensive literature search conducted in November 2013. Randomized controlled trials were selected and categorized according to the eligibility criteria established in the protocol. Results: 213 studies were identified as relevant to the scoping question. The number of eligible studies identified for each outcome were: bone health (14 studies), weight management and nutrition related health outcomes (81 studies), metabolic health (6 studies); cardiovascular health (57 studies); gastrointestinal health (24 studies); cancer (39 studies); diabetes (13 studies), Parkinson’s disease risk (3 studies), all-cause mortality (3 studies), skin complaints (3 studies), respiratory complaints (3 studies), joint pain/function (2 studies); the remaining 8 studies reported a variety of other outcomes. For studies of a similar design and which assessed the same outcomes in similar population groups, we report the potential for the combining of data across studies in systematic reviews. Conclusions: This scoping review has revealed the extensive evidence base for many outcomes which could be the focus of systematic reviews exploring the health effects of yogurt consumption.